IMPACT OF WORD-OF-MOUTH MARKETING ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN AFGHANISTAN - Mosavi, Hafizullah; Gunawan, Theresia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The objective of this research was to figure out the effect of word-of-mouth marketing on the overall performance of Afghan SMEs. The study employed a quantitative research approach, with data being gathered using a standardized questionnaire. Totally, 110 questionnaires were distributed by Google Forms to the owners of SMEs operating in Afghanistan. Collected data were then analyzed through regression tests and by SPSS version 23. Results from this study show that SMEs in Afghanistan benefit significantly from word-of-mouth marketing. Furthermore, the study's findings show that word-of-mouth marketing affects companies regardless of their employee numbers. The findings of the research hold significant value for SMEs owners, as they provide insights into how word-of-mouth marketing influences their companies.